Chiral Supraparticles for Controllable Nanomedicine. Issue 1 (5th November 2019) - Yeom, Jihyeon; Guimaraes, Pedro P. G.; Ahn, Hyo Min; Jung, Bo‐Kyeong; Hu, Quanyin; McHugh, Kevin; Mitchell, Michael J.; Yun, Chae‐Ok; Langer, Robert; Jaklenec, Ana
Abstract: Chirality is ubiquitous in nature and hard‐wired into every biological system. Despite the prevalence of chirality in biological systems, controlling biomaterial chirality to influence interactions with cells has only recently been explored. Chiral‐engineered supraparticles (SPs) that interact differentially with cells and proteins depending on their handedness are presented. SPs coordinated with d ‐chirality demonstrate greater than threefold enhanced cell membrane penetration in breast, cervical, and multiple myeloma cancer cells. Quartz crystal microbalance with dissipation and isothermal titration calorimetry measurements reveal the mechanism of these chiral‐specific interactions. Thermodynamically, d ‐SPs show more stable adhesion to lipid layers composed of phospholipids and cholesterol compared to l ‐SPs. In vivo, d ‐SPs exhibit superior stability and longer biological half‐lives likely due to opposite chirality and thus protection from endogenous proteins including proteases. This work shows that incorporating d ‐chirality into nanosystems enhances uptake by cancer cells and prolonged in vivo stability in circulation, providing support for the importance of chirality in biomaterials. Thus, chiral nanosystems may have the potential to provide a new level of control for drug delivery systems, tumor detection markers, biosensors, and other biomaterial‐based devices. Abstract : Incorporating d ‐chirality into supraparticles (SPs) enhances uptake by cancer cells and prolongs in vivo stability in circulation. These chiral‐selective interactions result from the energetically more favorable association of d ‐SPs with cells, which have the same handedness, compared with endogenous proteins and proteases with opposite handedness.